PCR-Based diagnostics in infectious disease (Cambridge, Massachusetts, 1993)
The book is the first comprehensive collection of PCR-based diagnostic methodologies for the detection of microbial infections. It is divided into three major interrelated sections: Section 1, the Clinical PCR Labiratory, is an introduction to PCR technology and the establishment of an effective lab; Section 2, PCR in Clinical Diagnostics, describes the role of PCR in diagnosing specific diseases, from the Epstein-Barr virus through sexually transmitted diseases; and Section 3, PCR-Based Protocols, explains the use of PCR technology in detecting specific organisms
Keywords: communicable diseases - diagnosis,polymerase chain reaction - diagnostic use,polymerase chain reaction - methods,virus diseases - diagnosis